TO CONDUCT A COMPARATIVE CHARACTERISTIC OF STIS IN RELATION TO THESE DISEASES DIAGNOSED - Toshev S.U.; Rafikova M.F.; Isaev X.D. (PEDAGOGS, 2024)
Abstract: The task set before us to write this article was identify the number of patients with sexually transmitted infections (STIs) treated in the department of dermatovenereology and cosmetology in 2017, analyze the structure of STIs for the selected period. Conduct a comparative analysis of these diseases diagnosed in 2016-2017. To achieve our goals and objectives, we conducted a retrospective analysis of the structure of registered cases of infections. As a result, we came to the conclusion that, according to the results of the analysis of the work of the department of dermatovenerology and cosmetology for 2017, it was established that among those who applied to the department, regardless of gender, the predominant number of patients were with anogenital (venereal) warts, then by frequency of applications followed by patients with chlamydial infection